2016
DOI: 10.1063/1.4966279
|View full text |Cite
|
Sign up to set email alerts
|

Circularly polarized lasing in chiral modulated semiconductor microcavity with GaAs quantum wells

Abstract: We report the elliptically, close to circularly polarized lasing at ω = 1.473 and 1.522 eV from an AlAs/AlGaAs Bragg microcavity with 12 GaAs quantum wells in the active region and chiral-etched upper distributed Bragg refractor under optical pump at room temperature. The advantage of using the chiral photonic crystal with a large contrast of dielectric permittivities is its giant optical activity, allowing to fabricate a very thin half-wave plate, with a thickness of the order of the emitted light wavelength,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Second, both from fundamental and practical viewpoints studies of chirality effects for excitons in two-dimensional materials interacting with light are very promising in view of recent predictions of substantial natural optical activity in TMDC MLs stacks 110 . Furthermore, realizations of combined systems with TMDC MLs embedded in chiral cavities open up possibilities of realizing room temperature circularly polarized lasing 111 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, both from fundamental and practical viewpoints studies of chirality effects for excitons in two-dimensional materials interacting with light are very promising in view of recent predictions of substantial natural optical activity in TMDC MLs stacks 110 . Furthermore, realizations of combined systems with TMDC MLs embedded in chiral cavities open up possibilities of realizing room temperature circularly polarized lasing 111 .…”
Section: Discussionmentioning
confidence: 99%
“…For CPL generation via nano-sized devices, various types of two- and three-dimensional metamaterials have been developed. Yet, the use of metamaterials invariably requires a complicated fabrication process with high precision. Other methods have also been suggested for direct generation of CPL, such as organic light-emitting diodes, vertical-cavity surface-emitting lasers, semiconductor quantum well lasers, and external-cavity lasers based on small organic molecules (SOMs). However, most of the methods mentioned above share the same issue of a complicated and delicate fabrication process to achieve them. In particular, it is worth noting that SOMs are natural materials that possess chirality in their structures, thereby exhibiting circular dichroic properties: Cerdán et al have demonstrated CPL emission by utilizing SOMs in conjunction with an external laser cavity, with a luminescence dissymmetry factor between 0.1 and 0.2. , Although this type of device can yield CPL emission, SOMs naturally have relatively small CD quantified with an extinction dissymmetry factor in the order of 10 –4 –10 –2 , , and the use of the external laser cavity moreover hinders the possibilities for using it in direct nano-photonic applications.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we studied a diamond metamembrane with "chiral morphology" of surface patterns. It is well known that chiral structures have great possibilities in circular polarization filtering (see [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 ]). One example involves three-dimensional chiral photonic crystals that show giant circular dichroism in the near-infrared range due to their polarization-dependent photonic stop bands [ 47 , 48 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike C symmetrical structures, metasurfaces with C symmetry demonstrate circular dichroism in transmission along the normal direction to the sample surface [ 52 ]. In references [ 41 , 42 , 43 , 44 , 45 ], the authors used C symmetrical metasurfaces to obtain the circularly polarized visible and near-infrared photoluminescence of semiconductor quantum dots. Due to the scalability of Maxwell’s equations, the wavelengths of optical resonances in C symmetrical metasurfaces can be shifted to the middle infrared by increasing their thickness and period.…”
Section: Introductionmentioning
confidence: 99%